Sosialisasi Pengaplikasi Centrifugal Force Dalam Memproduksi Minyak Kelapa Murni - Rudi Wardana; Abdurrahman Salim; Anni Nuraisyah; Setyo Andi Nugroho (Journal of Community Development, 2023)
Cooking oil is one of the staple ingredients that is widely used in household and industrial needs. The high price of cooking oil has an impact on the food security of a family. Repeated use of cooking oil will also have an impact on family health. So it is necessary to socialize the healthy and quality cooking oil using virgin coconut oil. The purpose of this socialization was directed to the group of housewives in Pumo Village, Wuluhan District, Jember Regency. The economic condition of this housewife is classified as lower middle class. The Pumo Village Housewives Group (partner) is located in a coastal area with extraordinary coconut potential. Utilization of coconut is only limited to being sold in the form of coconuts, either young (degan) or old (copra). Though the potential will be greater if the processing is carried out, especially in the form of pure coconut oil. The solution offered to this problem is the application of science and technology with simple technology, namely centrifugal force as an effort to become independent partners in producing virgin coconut oil. The virgin coconut oil produced is not only to support family food security, but also to be a business opportunity for partners. The results of this service, the community can know the techniques of making, packaging products and entrepreneurship in the field of making virgin coconut oil.